2007
DOI: 10.1002/lapl.200710087
|View full text |Cite
|
Sign up to set email alerts
|

Calculations regarding cell metabolism stimulation using photons in the visible wavelength range

Abstract: Abstract:The driving force behind the complex system of metabolism is based on the efficient use of potential differences. An intact biological system has a dynamic equilibrium in which the cellular biochemical reactions are in a pseudo-stationary state. The equilibrium can be manipulated by external effects such as, temperature changes brought about radiation absorption. Hot spots can be induced by the absorption of photons in strongly absorbing areas within the tissue or the sub-cellular components. Simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As well as that, they show that the interactions of the electromagnetic waves with the biological tissue cause the cells to warm up a little, including their mitochondrial membrane, leading to oxidative stress and triggering biochemical reactions that speed up the metabolism by increasing oxygen consumption 32 . A cell is usually able to overcome the effects of stress provided that the disturbances of the redox balance are small, restoring normal intracellular balance with positive stimulatory effects on the cells; largerscale disturbances, however, may be lethal to the cells [17][18][19] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As well as that, they show that the interactions of the electromagnetic waves with the biological tissue cause the cells to warm up a little, including their mitochondrial membrane, leading to oxidative stress and triggering biochemical reactions that speed up the metabolism by increasing oxygen consumption 32 . A cell is usually able to overcome the effects of stress provided that the disturbances of the redox balance are small, restoring normal intracellular balance with positive stimulatory effects on the cells; largerscale disturbances, however, may be lethal to the cells [17][18][19] .…”
Section: Discussionmentioning
confidence: 97%
“…More recent in vitro studies show that the action of low-intensity Laser can also be applied to repair and regenerate cartilages due to the biostimulation in the production of the cartilage matrix 32 . As well as that, they show that the interactions of the electromagnetic waves with the biological tissue cause the cells to warm up a little, including their mitochondrial membrane, leading to oxidative stress and triggering biochemical reactions that speed up the metabolism by increasing oxygen consumption 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The first challenge to the adhesive interface during adhesive restorative procedures is represented by the resistance to the stresses generated by polymerization shrinkage, specifically during the curing of polymeric materials [6][7][8]. Therefore, it is important that the immediate bond strength should be strong enough to withstand these stresses.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that LLLT causes biostimulatory effects on different cell types, characterized by increase in cell proliferation, metabolism, migration, and protein and gene expression [14][15][16]. It has also been shown that specific LLLT can penetrate tissues, promoting local biostimulation [17][18][19].…”
Section: Introductionmentioning
confidence: 99%